ANALYSIS OF THE ABILITY OF JUNIOR HIGH SCHOOL STUDENTS TO SOLVE THE PHYSICS PROBLEMS IN VARIOUS FORMS OF PROBLEM REPRESENTATIONS - Sutirta, I Wayan Gede; Muslimin, Muslimin; Pasaribu, Marungkil (IKIP Mataram, 2020)
This research is a descriptive study with a qualitative approach, which aims to describe the ability of junior high school students to solve physics problems in various forms of problem representation. The subjects in this study were the IX grade junior high school students in six Palu city schools. Respondents for interviews in the study amounted to 4 people for each form of problem representation, with the criteria of students who answered right, students who answered ± 50% correct, students who answered incorrectly, and who did not answer. The instrument used was a test of problem solving skills and interviews. The data obtained were analyzed qualitatively including data reduction, presenting data and verification while descriptive analysis was performed by calculating the total score, calculating the percentage and categorizing problem solving abilities. The results obtained by the average ability of junior high school students to solve physics problems in various forms of problem representation 21.86% (less category), with the percentage of each form of representation ie verbal representation 36.09% (less category), image/picture representation 23.78% (less category), diagram representation 19.47% (poor category) and graphic representation 8.10% (poor category).